Конструктивно-географічні засади системи управління екологічною безпекою природних і антропогенних геосистем - Приходько, М.М. (Український географічний журнал, 2011)
Изложены конструктивно-географические основы, формирующие подходы к управлению экологической безопасностью природных и антропогенных геосистем. Раскрыто содержание системы управления экологической безопасностью геосистем как сложной комплексной проблемы, названы основные составляющие ее блоки. Показаны пути достижения целей управления экологической безопасностью природных (содействие процессам самовосстановления) и антропогенных (оптимизация их территорий) геосистем, особенности выбора управленческих решений и мероприятий. The constructive-geographical bases, which determine approaches to the management of environmental safety of natural and anthropogenic geosystems are described. The content of the system of management of environmental safety of geosystems as a complex problem is considered, its main blocks are defined. The ways of achieving the goals of management of environmental safety of natural geosystems (assistance to self-recovering processes) and anthropogenic geosystems (optimization of their territories) are substantiated; the peculiarities of choice of management decisions and actions are shown.